wahkotowin: Reconnecting to the Spirit of nêhiyawêwin (Cree Language) - Napier, Kyle; Whiskeyjack, Lana (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2021)
The Spirit of the Language project looks to the Spirit of nêhiyawêwin (Cree language), sources of disconnection between nêhiyawak (Cree people) in Treaty 6 and the Spirit of nêhiyawêwin, and the process of reconnection to the Spirit of the language as voiced by nêhiyawak. The two researchers behind this project are nêhiyaw language-learners who identify as insider-outsiders in this work. The work is founded in Indigenous Research Methodologies, with a particular respect to ceremony, community protocol, consent, and community participation, respect and reciprocity. We identified the Spirit of the language as having three distinct strands: history, harms, and healing. The Spirit of Indigenous languages is dependent on its history of land, languages, and laws. We then identified the harms or catalysts of disconnect from the Spirit of the language as colonization, capitalism, and Christianity. The results of our community work have identified the methods for healing, or reconnecting to the Spirit of language, by way of autonomy, authority, and agency.